Notes on scythridid moths in Habahu National Nature Reserves, with description of one new species (Lepidoptera: Scythrididae) - Lou, Kang; You, Wanxue; Huang, Zhilin; Li, Houhun (Zootaxa, 2018)
In a faunal study of insects in the Habahu National Nature Reserves of Ningxia, seven species of the genus Scythris of Scythrididae are recognized. One species, S. fustivalva Li, sp. nov., is described as new; five species are newly recorded in China: S. caballoides Nupponen, 2009, S. mikkolai Sinev, 1993, S. orientella Sinev, 2001, S. pallidella Passerin d’Entrèves et Roggero, 2006 and S. sinevi Nupponen, 2003. Photos of adults and genitalia are provided, and a list of Scythrididae in China is given.